A PUSH AND PULL INTERVENTION TO CONTROL AVIAN INFLUENZA: A LESSON LEARNED FROM THE WESTERN JAVA POULTRY SECTOR - Dikky Indrawan; Arjan Stegeman; Arief Daryanto; Henk Hogeveen (Jurnal Manajemen & Agribisnis, 2019)
HPAI H5N1 is considered endemic in Indonesian poultry and poses a major challenge to animal and human health authorities. The complex structure of the Indonesian poultry meat value chain is an important reason for the limited efficacy of HPAI control in Indonesia so far. The paper objective is to describe how to implement a push-and-pull strategy in the poultry supply chain to control HPAI infection in Western Java. More specifically, this study investigates the poultry value chain in Western Java in relation to consumers’ behavior and governance of the value chain. Implementation of biosecurity and HPAI control measures was strongly related to the governance structure of the chain, with interactions that accentuating the risk of HPAI. In conclusion, a push strategy, as an incentive mechanism, should be designed in such a way that it pays attention to the interactions between actors in a value chain and their impact on introduction and transmission of disease. Moreover, a pull strategy as an incentive mechanism for consumers forcing producers to improve their production environment into higher levels of biosecurity is expected to be less effective than a push strategy targeting producers. Keywords: avian influenza, biosecurity, consumer preferences, willingness to pay, a push and pull strategy